2013
DOI: 10.1021/ic402432q
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromism, the Alexandrite Effect, and Dynamic Jahn–Teller Distortions in Ho2Cu(TeO3)2(SO4)2

Abstract: A 3d-4f heterobimetallic material with mixed anions, Ho2Cu(TeO3)2(SO4)2, has been prepared under hydrothermal conditions. Ho2Cu(TeO3)2(SO4)2 exhibits both thermochromism and the Alexandrite effect. Variable temperature single crystal X-ray diffraction and UV-vis-NIR spectroscopy reveal that changes in the Cu(II) coordination geometry result in negative thermal expansion of axial Cu-O bonds that plays a role in the thermochromic transition of Ho2Cu(TeO3)2(SO4)2. Magnetic studies reveal an effective magnetic mom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…7 Thermal expansion of axial Cu–O bonds in the 3d–4f hetero-bimetallic complex, Ho 2 Cu(TeO 3 ) 2 (SO 4 ) 2 , with temperature exhibited reversible thermochromism. 8 Single-crystal-to-single-crystal (SCSC) transformation via dehydration and rehydration of the mixed-metal complex, [Co 2 (ppca) 2 (H 2 O)(V 4 O 12 ) 0.5 ], exhibited reversible thermochromism between red and brown. 9 Fu and co-workers have reported low-temperature thermochromism in various iodometallate-based inorganic–organic hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…7 Thermal expansion of axial Cu–O bonds in the 3d–4f hetero-bimetallic complex, Ho 2 Cu(TeO 3 ) 2 (SO 4 ) 2 , with temperature exhibited reversible thermochromism. 8 Single-crystal-to-single-crystal (SCSC) transformation via dehydration and rehydration of the mixed-metal complex, [Co 2 (ppca) 2 (H 2 O)(V 4 O 12 ) 0.5 ], exhibited reversible thermochromism between red and brown. 9 Fu and co-workers have reported low-temperature thermochromism in various iodometallate-based inorganic–organic hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…Great success has been achieved in the tellurite–sulfate system, as numerous actinides, lanthanides, transition metals, and even heterobimetallic complexes have been synthesized hydrothermally. Examples of these include M­(TeO 3 )­(SO 4 ) (M = Th, Pu), , Ln 2 (Te 2 O 5 )­(SO 4 ) 2 (Ln = La to Lu, except Pm, Dy, and Ho), Ho 3 (TeO 3 ) 2 (SO 4 ) 2 (OH)­(H 2 O), Ln 2 TeO 3 (SO 4 ) 2 (H 2 O) 2 (Ln = Er to Lu), M 3 (TeO 3 )­(SO 4 )­(OH) 2 ·2H 2 O (M = Ni, Co), M 2 (TeO 3 )­(SO 4 )·H 2 O (M = Co, Mn), and Ln 2 M­(TeO 3 ) 2 (SO 4 ) (Ln = Y, Nd to Lu, except Pm; M = Cu, Co, or Zn). Iodate and tellurite anions both adopt trigonal-pyramidal geometries due to the presence of a stereochemically active lone pair of electrons on I/Te centers. Selenium and sulfur belong to the chalcogen group, and their oxyanions SeO 4 2– /SO 4 2– adopt an identical tetrahedral geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Tellurite anions are known to have high polarizability and form unique structural topologies. Their variable coordination modes are due to the stereoactive lone pair (SALP) of electrons on the Te IV metal centers. ,, Several studies have suggested that the presence of SALP electrons in oxoanion systems is ideal for the formation of cationic materials because they yield highly distorted metal centers with the O atoms pushed off to the sides. , These observations give this system many favorable attributes for the formation of cationic materials. Herein, we report on the hydrothermal preparation and structural elucidation of a new purely inorganic d/f-heterometallic cationic material, [Ag 2 M­(Te 2 O 5 ) 2 ]­SO 4 (M = Ce IV or Th IV ).…”
mentioning
confidence: 99%
“…Tellurium, because of its SALP electrons and polarizability, can form polymeric structures, resulting in highly variable coordination environments. This is due to tellurium’s ability to bind three, four, or five O atoms and form a variety of building units such as 1D chains, 2D sheets, and 3D frameworks. ,, …”
mentioning
confidence: 99%